Sua muham̐ra patara - Dāsa, Śrīdhara (Utkaḷa Biśvabidyāḷaẏa grantha, 2002)
Autobiographical reminiscences of an Oriya educationist and, former vice-chancellor of Utkal University, Orissa; publication sponsored by Utkal University, Orissa